The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.21511/ppm.17(4).2019.08
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the national tourism system on the economic growth in Ukraine

Abstract: The paper aims at analyzing the impact of tourism on the economic growth in Ukraine considering its global significance and dynamic development. Tourism should be considered not as a separate phenomenon, but as a complex socio-economic-ecological system, i.e. the national tourism system (NTS). The study attempts to reveal the nature and determinants of the national tourism system impact on economic growth, and also empirically substantiates this in the Ukrainian context. Since the economic decisions require a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Researchers identified that tourism has a beneficial effect on economic and social growth in the Issyk-Kul region of the Kyrgyz Republic, 2002-2017, and that this influence is increasing every year. Mazaraki et al (2019), on the example of Ukraine (data 2000-2017) confirm the overall fact that tourism has a positive influence on economic growth.…”
Section: Literature Reviewmentioning
confidence: 62%
“…Researchers identified that tourism has a beneficial effect on economic and social growth in the Issyk-Kul region of the Kyrgyz Republic, 2002-2017, and that this influence is increasing every year. Mazaraki et al (2019), on the example of Ukraine (data 2000-2017) confirm the overall fact that tourism has a positive influence on economic growth.…”
Section: Literature Reviewmentioning
confidence: 62%
“…The scientific literature discusses methods of assessing financial security by the bankruptcy criterion (Orlova, 2008;Coval et al, 2009;Portnova & Antonenko, 2012;Williams, 2014;Mazaraki et al, 2019), the disadvantage of which is the limited scope of diagnostics. Attempts to build an integral indicator (Tereshchenko, 2006;Matviychuk, 2007;Kuzenko et al, 2010;Piatnytska & Fedulova, 2020;Kharchuk et al, 2021) do not take into account the industry boundaries of the parameters in the calculations and all possible assessment indicators.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Currently, "digitalization brings the challenge to hotels' work process" (Buer, 2019, p. 6), and "the hotel industry strategically responds to digital platform power" (Balsiger et al, 2021). In the post-pandemic period, digitalization will become one of the main strategic concepts in the tourism and hotel business (Melnychenko et al, 2020;Mazaraki et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%